Development of multi-walled carbon nanotubes-based coatings on carbon-bonded alumina filters for steel melt filtration. Issue 5 (May 2015) - Storti, Enrico; Emmel, Marcus; Dudczig, Steffen; Colombo, Paolo; Aneziris, Christos G.
Abstract: Ceramic foam filters (CFFs) have been used by steel foundries for several years to remove non-metallic inclusions from the metal castings. In order to improve their filtration efficiency, promising approaches which involve "active" and "reactive" coatings applied on the filters have recently been proposed. In this work, a new coating system containing multi-walled carbon nanotubes (MWCNTs) is presented. A special water-based dispersing technique for carbon nanotubes was developed. Xanthan gum was used both as a dispersing agent and as a rheology modifier for the spraying slurries. The synthetic coal tar pitch Carbores ® P was added as a binder for the carbon nanotubes. The coatings were cold-applied on 10 pores per inch (ppi) carbon-bonded alumina filters previously manufactured via the Schwartzwalder process. After drying, the samples were heat treated at 800 °C. The performance of the coated filters was investigated with the aid of a special steel casting simulator in fully-controlled atmosphere.